The Application of Virtual Reality Technology to Enhance Students’ Chorus Conducting Performance in a Technology Institute in Southeast China - Ge, Tian; Phongsatha, Thanawan; Achwarin, Naree (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This research aimed to investigate the effectiveness of the application of VR technology as a supplementary tool for enhancing students' chorus conducting performance and determining the students' satisfaction with using VR technology to enhance students' chorus conducting performance. A mixed research design was used for this study: quasi-experiment as quantitative research and face-to-face interview as qualitative research. The participants in this study were 60 music students at Changshu Institute of Technology. Aged 18- 20 years and are music teacher majors. The participants in the quasi-experiment were divided into two groups: 30 participants for the control group and 30 participants for the experimental group. Ten students were recruited from the experimental group to conduct face-to-face interview. A traditional classroom was used for the control group and blended learning with VR technology integration was developed as a supplement for the experimental group. The researcher employed an independent sample T-test to test the hypotheses and content analysis to analyze qualitative data. The results revealed that four variables had higher scores and there was significant improvement in the conducting skills of students in the experimental group than in the control group. The results revealed that blended learning using VR technology serves as an effective learning tool to improve student chorus conducting performance. The students presented a positive reflection and satisfaction toward using VR technology to enhance students' chorus conducting performance throughout the teaching and learning process.